2012
DOI: 10.1017/s1751731111001790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meloxicam (Metacam®) on post-farrowing sow behaviour and piglet performance

Abstract: Farrowing is an intrinsically risky process for both the sow and the piglets that can cause welfare and economic problems. The effects of the non-steroidal anti-inflammatory drug meloxicam on post-farrowing behaviour of sows, and the performance of piglets were investigated. A total of 48 sows were randomly allocated at the day of farrowing (day 0) into two homogeneous groups regarding parity, and treated with either meloxicam or saline solution as placebo. For each sow, number of position changes, total time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 54 publications
(65 reference statements)
8
33
2
Order By: Relevance
“…The frequencies of posture changes and durations of postural behavior have been used in assessing pain in sows arising from farrowing (95–97, 99101), the presence of shoulder ulcers (73), and lameness (82, 90, 98). Naloxone (an opioid antagonist) administration increased standing, lying ventrally, and postural changes in periparturient sows, indicating that endogenous opioids may have a role in reducing pain at farrowing, which is manifest by frequent posture changes (101).…”
Section: Pain Assessment In Pigsmentioning
confidence: 99%
See 3 more Smart Citations
“…The frequencies of posture changes and durations of postural behavior have been used in assessing pain in sows arising from farrowing (95–97, 99101), the presence of shoulder ulcers (73), and lameness (82, 90, 98). Naloxone (an opioid antagonist) administration increased standing, lying ventrally, and postural changes in periparturient sows, indicating that endogenous opioids may have a role in reducing pain at farrowing, which is manifest by frequent posture changes (101).…”
Section: Pain Assessment In Pigsmentioning
confidence: 99%
“…In contrast, Lawrence et al (102) recorded decreased frequency and duration of standing in naloxone-treated sows. Posture and the number of posture changes have been used to evaluate the use of post-farrowing analgesics (95–97, 100). Haussmann et al (100) demonstrated that sows administered butophanol for 3 days post-parturition adopted fewer body position changes between 48 and 72 h afterward.…”
Section: Pain Assessment In Pigsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, data were not documented during parturition itself according to criteria defined beforehand, but data were collected retrospectively from several farms with different management methods of parturition by means of a questionnaire [11,5]. On the other hand, dystocia rates were related to the number of manually developed piglets, or duration of parturition was selected as a criterium for dystocia [31,14,32].…”
Section: Discussionmentioning
confidence: 99%